Lesser Toxicities of Belotecan in Patients with Small Cell Lung Cancer: A Retrospective Single-Center Study of Camptothecin Analogs - Yeon Hee Park; Chae Uk Chung; Bo Mi Park; Myoung Rin Park; Dong Il Park; Jae Young Moon; Hee Sun Park; Jin Hwan Kim; Sung Soo Jung; Ju Ock Kim; Sun Young Kim; Jeong Eun Lee (Canadian Respiratory Journal)
Purpose. Topotecan and belotecan are camptothecin derivatives that are used to treat small cell lung cancer (SCLC). This study compared the toxicities and efficacies of belotecan and topotecan monotherapies in patients with SCLC. Methods. We retrospectively reviewed data from 94 patients with SCLC (with or without prior chemotherapy) who were treated using belotecan monotherapy (n=59, 188 cycles) or topotecan monotherapy (n=35, 65 cycles) between September 2003 and December 2011. Results. Thrombocytopenia occurred during 42% and 61.5% of the belotecan and topotecan cycles, respectively (p=0.007). Significant differences between belotecan and topotecan were also observed for grade 4/5 lung infection (3.2% versus 10.8%, resp.; p=0.003), all-grade headache (3.2% versus 10.8%, resp.; p=0.017), and grade 4/5 increased liver enzymes (0.5% versus 4.6%, resp.; p=0.023). The median TTPDs, CSSs, and OSs were 14 months and 11.6 months (p=0.646), 10 months and 7 months (p=0.179), and 34.5 months and 21.4 months (p=0.914) after belotecan and topotecan monotherapy, respectively. Conclusions. Belotecan monotherapy may be safer than topotecan monotherapy in SCLC patients. And in terms of efficacy, belotecan could be comparable to topotecan monotherapy.